Carbon negative electrode material with high initial coulombic efficiency and preparation method and application thereof

By accurately controlling specific oxygen-containing functional groups on the surface of the carbon negative electrode material, an efficient screening interface mask was formed, which solved the problem of low efficiency of sodium ion batteries for the first time, and achieved efficient sodium ion storage and solvent separation, improving battery performance.

CN120504315APending Publication Date: 2025-08-19NAKUN CARBON SOURCE (TIANJIN) TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202510535079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-01
Filing Date
2025-04-27
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

The carbon anode material of existing sodium ion batteries has low efficiency for the first time, making it difficult to achieve effective storage of sodium ions and screening of solvents, resulting in poor battery performance.

Method used

The implantation of specific oxygen-containing functional groups, such as lactone groups and carboxylic anhydrides, is accurately regulated on the surface of the carbon anode material, and a carbon material with a high specific surface area is formed through reduction and grafting, forming a highly efficient screening interface film to promote sodium ions storage and block solvent decomposition.

Benefits of technology

The first Coulomb efficiency of sodium ion batteries was significantly improved to 98.6%, and the cycle stability was improved. The interface film formation was accelerated through the directional implantation of specific functional groups, achieving efficient sodium ion storage and screening of solvent molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120504315A_ABST
    Figure CN120504315A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion batteries, in particular to a carbon negative electrode material with high first coulombic efficiency and a preparation method and application thereof.The carbon negative electrode material with the high first coulombic efficiency is characterized in that an oxygen-containing functional group is implanted into the surface and is a specific functional group capable of being precisely regulated and controlled, and the oxygen-containing functional group is a specific functional group capable of being precisely regulated and controlled; the specific functional group comprises a lactone group and carboxylic acid anhydride, and the ratio of the lactone group to the carboxylic acid anhydride is 64%-87%; according to the invention, by implanting a precisely regulated and controlled specific functional group into the surface of the carbon negative electrode material, the construction of the screening type interfacial film is accelerated, the obtained screening type interfacial film has efficient screening capability, and can realize the transmembrane storage of sodium ions, and solvent molecules are blocked and shielded, so that the irreversible side reaction caused by decomposition is avoided; the technical problem that a screening type interface film in an existing sodium ion battery is difficult to realize transmembrane storage of sodium ions and screening of a solvent at the same time is solved, and the first coulombic efficiency of the sodium ion battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a carbon negative electrode material with high initial coulombic efficiency, a preparation method thereof, and an application thereof. Background Art

[0002] With the global energy transition and growing demand for new energy technologies, sodium-ion batteries (Na-ion batteries) have shown broad application prospects due to their abundant resources, low cost, and superior low-temperature and fast-charging characteristics. They are considered a potential alternative to lithium-ion batteries. Carbon-based materials have become a popular choice for battery anode materials due to their excellent conductivity, thermal stability, and relatively low cost.

[0003] Currently, a variety of carbon-based anode materials are being used in sodium-ion batteries on the market, including but not limited to hard carbon, soft carbon, and graphene-based materials. While these traditional carbon materials have demonstrated a certain degree of feasibility, they still suffer from issues such as poor initial coulombic efficiency, low specific capacity, and poor rate performance.

[0004] The poor first coulombic efficiency of existing sodium-ion batteries is due to the fact that the reversibility of the electrochemical storage of sodium ions on the carbon negative electrode is often plagued by carbon structural defects. Although the structural defects and functional groups of the carbon negative electrode increase the adsorption energy of sodium ions, the high adsorption energy can easily produce a "trap effect", making it more difficult for sodium ions to escape from the defects and functional groups. They will undergo irreversible parasitic interfacial reactions with the solvent in the electrolyte. The resulting solid electrolyte membrane (SEI) has poor stability and weak interfacial solvent and sodium ion screening capabilities, resulting in a decrease in the first coulombic efficiency, thereby restricting the application of carbon material negative electrodes.

[0005] In recent years, researchers have tried to modify carbon materials by various means, but most of them are aimed at hard carbon materials in a broad sense, whose specific surface area is less than 100m 2 g -1 In a broad sense, hard carbon materials are difficult to graphitize, and their heat treatment temperature is relatively high, generally 1000-2000℃. Figure 1 As shown in the figure: Carbon microcrystals that are difficult to graphitize will form abundant closed pores, which cannot be characterized by the nitrogen adsorption specific surface area. The sodium storage process of hard carbon is generally manifested as adsorption-closed pore filling. Its main working voltage curve has a slope region (2~0.1V) and a platform region (0.1~0V). The slope region reflects the adsorption behavior of sodium ions on hard carbon defects and edges, and the platform region reflects the filling behavior of sodium ions in hard carbon closed pores, forming sodium metal clusters.

[0006] In comparison, high surface area carbons, mainly graphene and porous carbon, have a large number of open surfaces or open pore structures, with high surface area and sodium ion storage mechanisms that rely on surface adsorption. For example, the two-dimensional structure of graphene has a high surface area (200m 2 g -1 ~2000m 2 g -1 ), porous carbon can have a variety of open pore structures, including micropores, mesopores, and macropores. Therefore, its charge-discharge curve is characterized by a single slope (3-0V), corresponding to the adsorption of sodium ions on the surface. Surface adsorption behavior of sodium ions can easily lead to irreversible adsorption, resulting in irreversible capacity loss. At the same time, its high porosity can cause excessive electrolyte decomposition, resulting in low initial coulombic efficiency.

[0007] Existing technologies all regulate the structure of the electrolyte or carbon negative electrode materials, and introduce more functional sites that are conducive to sodium storage through physical activation, chemical oxidation or doping with other elements. For example, Yu's team synthesized porous carbon with controllable porous structure and no structure required, which was 9.6Ag -1 Even at a current density of 66 mAh g -1 The existing technology has excellent rate performance, but the first coulombic efficiency is less than 60%. Although the existing technology changes the chemical state of the material surface and increases the sodium storage capacity, the SEI membrane formed thereby is difficult to simultaneously achieve transmembrane storage of sodium ions and screening of solvents, and does not have the ability of efficient screening. The first coulombic efficiency and cycle stability of the obtained sodium ion battery are poor. Summary of the Invention

[0008] In order to solve the problem of low first coulombic efficiency of the above-mentioned carbon negative electrode material, the present invention provides a carbon negative electrode material with high first coulombic efficiency and its preparation method and application, which significantly improves the first coulombic efficiency.

[0009] The present invention provides a carbon negative electrode material with high first coulombic efficiency, which is obtained by implanting oxygen-containing functional groups on the surface of the carbon material. The oxygen-containing functional groups are precisely regulated specific functional groups, which include lactone groups and carboxylic anhydrides, and the lactone groups and carboxylic anhydrides account for 64% to 87%.

[0010] Furthermore, the specific functional groups also include carboxyl groups, and the proportion of the carboxyl groups is 1% to 10%, preferably 1.8% to 5%.

[0011] Furthermore, the specific surface area of the carbon material is 200m 2 g -1 ~2000m 2 g -1 , the carbon material includes at least one of graphene, carbon nanotubes, porous carbon, microporous carbon and mesoporous carbon.

[0012] Furthermore, the oxygen-containing functional groups account for 3.3% to 23.1% of oxygen atoms in the carbon negative electrode material.

[0013] The present invention also provides a method for preparing the above-mentioned carbon negative electrode material with high first coulombic efficiency, including reduction treatment and grafting treatment of the carbon material surface, wherein the grafting treatment is to implant precisely controlled specific functional groups under a mixed atmosphere, wherein the mixed atmosphere includes an oxidizing atmosphere and a non-oxidizing atmosphere, and the volume of the oxidizing atmosphere accounts for 10-30% of the total volume of the mixed atmosphere.

[0014] Furthermore, the oxidizing atmosphere includes at least one of oxygen, carbon monoxide, water vapor and ozone; and the non-oxidizing atmosphere includes at least one of nitrogen, argon and hydrogen.

[0015] Furthermore, the grafting treatment temperature is 200-550° C., and the time is 0.5-2 h.

[0016] Furthermore, the reduction treatment is carried out in an inert gas atmosphere, at a reduction temperature of 500° C. to 1000° C., for a time of 2 to 4 hours.

[0017] The present invention also provides an application of the above-mentioned carbon negative electrode material with high first coulombic efficiency directly as a carbon negative electrode in a sodium ion battery.

[0018] Furthermore, the sodium ion battery also includes an electrolyte, which is a composite electrolyte containing a sodium salt and an organic solvent.

[0019] Furthermore, the sodium salt includes at least one of sodium trifluoromethanesulfonate, sodium perchlorate and sodium hexafluorophosphate; and the organic solvent includes at least one of methyl carbonate, ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0020] Furthermore, there is a sieving type interface film between the carbon negative electrode material and the composite electrolyte, and the sieving type interface film is formed by the contact reaction between the carbon negative electrode material and the composite electrolyte on the carbon surface, and includes organic components and inorganic components.

[0021] Furthermore, the carbon negative electrode material can accelerate the formation of the screening interface film on the carbon surface, and the film formation kinetics is better. The Tafel slope of the film formation reaction is reduced from 70 to 90 mV dec. -1 Reduced to 40-60mV dec -1 .

[0022] Furthermore, the organic component includes at least one of sodium alcoholate, alkyl carbonate, ester polymer and ether polymer; and the inorganic component includes at least one of sodium oxide, sodium carbonate, sodium fluoride and sodium sulfonate.

[0023] The present invention also provides the carbon negative electrode material with high initial coulombic efficiency, which is indirectly used as a negative electrode additive of a sodium ion battery and is used in combination with other carbon material negative electrodes.

[0024] Furthermore, the carbon material used as a negative electrode additive for sodium ion batteries is a hard carbon material.

[0025] Preferably, the hard carbon material comprises a specific surface area of 5-30m 2 g -1 Biomass hard carbon materials, such as coconut shell hard carbon and walnut shell hard carbon.

[0026] Preferably, the hard carbon material also includes a specific surface area of 0-20m 2 g -1 molecular sieve hard carbon materials.

[0027] The advantages of the present invention are:

[0028] 1. Different from the sodium storage mechanism of hard carbon material adsorption-closed pore filling in a broad sense, the carbon negative electrode material used in the present invention is a graphitized carbon material with a surface area of 200m 2 g -1 ~2000m 2 g -1 , showing high specific surface area carbon, with a large number of open surfaces or open-pore structures, and having a sodium ion storage mechanism through high specific surface area and relying on surface adsorption; the reduction pretreatment temperature of the graphitizable carbon material used in the present invention is low, and the surface heteroatoms can be removed at low temperature to form a clean surface, which has high selectivity, and is convenient for subsequent grafting treatment to selectively achieve precise control of the types and proportions of specific functional groups on the carbon surface; at the same time, a mixed atmosphere is used to carry out grafting treatment on the surface of the carbon negative electrode, and by controlling the composition, proportion and grafting temperature of the mixed atmosphere to achieve selective oxidation, lactone groups, carboxylic anhydride and carboxyl groups are implanted on the negative electrode surface and their proportions are controlled, thereby achieving precise control of specific functional groups on the surface of the carbon negative electrode material;

[0029] 2. In sodium ion batteries, the specific functional groups implanted on the surface of the carbon material in the present invention are Lewis strong acids in the solution, which can quickly combine with the sodium ions in the composite electrolyte and have a strong adsorption force, which can enhance the adsorption of intermediates. The Tafel slope of the film-forming reaction is 70-90 mV dec. -1 Reduced to 40-60mV dec -1, accelerating the formation of a screening interface film on the carbon surface. The resulting interface film has the ability of efficient screening, which can achieve the storage of sodium ions through the membrane while blocking and shielding solvent molecules, avoiding decomposition and irreversible side reactions, greatly improving the first coulombic efficiency and cycle stability of sodium ions. Compared with the existing technology, the first coulombic efficiency of the sodium ion battery provided by the present invention is as high as 98.6%;

[0030] 3. In sodium ion batteries, the carbon negative electrode material with high first coulombic efficiency of the present invention can also be used as an electrode additive. By adding the carbon negative electrode material of the present invention to the negative electrode, the negative electrode can quickly form a screening carbon surface with high-efficiency screening ability, thereby reducing the loss of sodium ions. This can be used to improve the first coulombic efficiency of the carbon negative electrode of the sodium ion battery. Compared with the existing technology, this provides a new method for enhancing the first coulombic efficiency of the carbon negative electrode material of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the sodium storage difference between the carbon material of the present invention and the hard carbon material in the prior art in a broad sense;

[0032] Figure 2 This is the first charge and discharge curve diagram of Example 1 of the present invention;

[0033] Figure 3 This is a graph showing the test results of the oxygen atom ratio in Example 1 of the present invention;

[0034] Figure 4 1 is a graph showing the relative content of oxygen-containing functional groups in Example 1 of the present invention;

[0035] Figure 5 is the thermogravimetric loss curve of Example 1 of the present invention;

[0036] Figure 6 This is the first charge and discharge curve of Comparative Example 1;

[0037] Figure 7 This is the first charge and discharge curve of Comparative Example 2;

[0038] Figure 8 It is a comparison diagram of the Tafel curve of graphene with precise control of specific functional groups according to the present invention and the Tafel curve of uncontrolled graphene. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0040] It should be noted that the various installation methods and technical terms mentioned in the present invention are technical terms that have long been clearly known in the relevant technical field and therefore will not be further explained. In addition, the same reference numerals are used for the same components, but this does not affect nor constitute an accurate understanding of the technical solution by those skilled in the art.

[0041] Example 1

[0042] The carbon negative electrode material with high initial coulombic efficiency provided in this embodiment is prepared by the following preparation process:

[0043] Step 1: In a nitrogen atmosphere at a temperature of 900°C, a carbon material (the carbon material in this embodiment is graphene with a specific surface area of 502 m 2 g -1 ) and subjected to reduction treatment for 2 h to obtain a carbon negative electrode precursor;

[0044] Step 2: Graft the carbon negative electrode precursor obtained in step 1 under a mixed atmosphere at a temperature of 500°C (the mixed atmosphere in this embodiment is composed of 78% N2 and 22% O2). The grafting treatment time is 1 hour, so that the surface of the carbon negative electrode precursor is connected with precisely controlled specific functional groups.

[0045] XPS analysis of the carbon negative electrode material obtained in Example 1 was performed using a PHI 5000Versa Probe II spectrometer (Al Kα). The results are shown in Figure 2. Figure 3 As shown, the oxygen atom ratio of the obtained carbon negative electrode material is 10.6%, and the O1s spectrum analysis is performed, and the results are as follows Figure 4 As shown, the precisely controlled specific functional groups implanted on the surface of the obtained carbon material are lactone, carboxylic anhydride and carboxyl groups, with lactone and carboxylic anhydride accounting for 84% and carboxyl groups accounting for 2.6%.

[0046] The high initial coulombic efficiency sodium ion battery carbon negative electrode material of this embodiment is assembled into a sodium ion half-cell, and the specific process is as follows:

[0047] (1) The carbon negative electrode material obtained in this example, conductive carbon black (Super-P) having a conductive function, polyvinylidene fluoride (PVDF) having a bonding function, and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 8:1:1:100, the mixed material was coated on the surface of a copper foil, and then placed in an oven and vacuum-dried at 110° C. for 12 hours to obtain an electrode sheet, and the obtained electrode sheet was made into a circular electrode sheet with a diameter of 12 mm;

[0048] (2) The circular electrode sheet obtained in step (1) was assembled with sodium metal, 100 μL of a composite electrolyte (the electrolyte composition of this embodiment is diethylene glycol dimethyl ether and sodium trifluoromethanesulfonate, and the concentration of sodium trifluoromethanesulfonate is 1 mol / L), and a diaphragm to obtain a sodium ion half-cell.

[0049] Example 2

[0050] The preparation method of the carbon negative electrode material with high initial coulombic efficiency in this embodiment is the same as that in Example 1, except that the selection of the carbon material and the parameter conditions of the preparation process are different (as shown in Table 1):

[0051] The carbon material in this embodiment is microporous carbon with a specific surface area of 2000m 2 g -1 ;

[0052] In step 1, the reduction treatment temperature in this embodiment is 1000° C. and the time is 4 hours;

[0053] In step 2, the mixed atmosphere composition of the grafting treatment in this embodiment is 80% N2 and 20% O2; the grafting treatment temperature is 400°C and the time is 1 hour.

[0054] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 6.3%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups, among which the relative content of lactone groups and carboxylic acid anhydride groups was 77.7%, and the proportion of carboxyl groups was 3.9%.

[0055] The preparation process of assembling the carbon negative electrode material with high first coulombic efficiency into a sodium ion half-cell in this embodiment is the same as that in Example 1, except that the electrolyte in this embodiment is dimethyl ether, diethylene glycol dimethyl ether and sodium trifluoromethanesulfonate, the concentration of sodium trifluoromethanesulfonate is 1 mol / L, and dimethyl ether and diethylene glycol dimethyl ether are (50%:50%).

[0056] Example 3

[0057] The preparation method of the carbon negative electrode material with high initial coulombic efficiency in this embodiment is the same as that in Example 1, except that the selection of the carbon material and the parameter conditions of the preparation process are different (as shown in Table 1):

[0058] The carbon material in this embodiment is porous carbon with a specific surface area of 600 m 2 g -1 ;

[0059] In step 2, the grafting treatment temperature in this embodiment is 300° C. and the time is 2 hours.

[0060] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 3.8%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups, among which the relative content of lactone groups and carboxylic acid anhydride groups was 71.7%, and the proportion of carboxyl groups was 4.4%.

[0061] The preparation process of assembling the high first coulombic efficiency sodium ion battery carbon negative electrode material into a sodium ion half-cell in this embodiment is the same as that in Example 1, except that the electrolyte in this embodiment is tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether and sodium hexafluorophosphate, the concentration of sodium hexafluorophosphate is 1 mol / L, tetraethylene glycol dimethyl ether and diethylene glycol dimethyl ether (50%:50%).

[0062] Example 4

[0063] The preparation method of the high initial coulombic efficiency sodium ion battery carbon negative electrode material of this embodiment is the same as that of Example 1, except that the selection of carbon material and the parameter conditions of the preparation process are different (as shown in Table 1):

[0064] The carbon material in this embodiment is mesoporous carbon with a specific surface area of 1200 m 2 g -1 ;

[0065] In step 1, the reduction treatment time in this embodiment is 4 hours;

[0066] In step 2, the grafting treatment temperature in this embodiment is 500° C., and the heat treatment time is 0.5 h.

[0067] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 7.6%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, and carboxylic acid anhydride, among which the relative content of lactone groups and carboxylic acid anhydride was 79.3%.

[0068] The preparation process of assembling the high first coulombic efficiency sodium ion battery carbon negative electrode material into a sodium ion half-cell in this embodiment is the same as that in Example 1, except that the electrolyte in this embodiment is diethylene glycol dimethyl ether and sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate is 1 mol / L.

[0069] Example 5

[0070] The preparation method of the high initial coulombic efficiency sodium ion battery carbon negative electrode material of this embodiment is the same as that of Example 1, except that the selection of carbon material and the parameter conditions of the preparation process are different (as shown in Table 1):

[0071] The carbon material in this embodiment is carbon nanotubes with a specific surface area of 400 m 2 g -1 ;

[0072] In step 1, the reduction treatment temperature in this embodiment is 800° C. and the heat treatment time is 4 h;

[0073] In step 2, the oxidizing atmosphere composition of the grafting treatment in this embodiment is 70% N2 and 30% O2; the grafting treatment temperature is 500°C and the time is 2 hours.

[0074] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 23.1%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups. Among them, the relative content of lactone groups and carboxylic acid anhydride groups was 62.7%, and the proportion of carboxyl groups was 1.8%.

[0075] The preparation process of assembling the high first coulombic efficiency sodium ion battery carbon negative electrode material into a sodium ion half-cell in this embodiment is the same as that in Example 1, except that the electrolyte in this embodiment is ethylene carbonate, diethyl carbonate, and sodium perchlorate, the concentration of sodium perchlorate is 1 mol / L, and ethylene carbonate and diethyl carbonate are (50%:50%).

[0076] Example 6

[0077] The preparation method of the high initial coulombic efficiency sodium ion battery carbon negative electrode material of this embodiment is the same as that of Example 1, except that the selection of carbon material and the parameter conditions of the preparation process are different (as shown in Table 1):

[0078] In step 1, the reduction treatment temperature in this embodiment is 800° C. and the time is 4 h;

[0079] In step 2, the oxidizing atmosphere composition of the grafting treatment in this embodiment is 90% Ar2 and 10% O2; the grafting treatment temperature is 500°C and the time is 2 hours.

[0080] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 5.9%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups, among which the lactone groups and carboxylic acid anhydride groups accounted for 80.3%, and the carboxyl groups accounted for 4.9%.

[0081] The preparation process and electrolyte of the high first coulombic efficiency sodium ion battery carbon negative electrode material assembled into a sodium ion half-cell in this embodiment are the same as those in Example 1.

[0082] Example 7

[0083] The preparation method and carbon negative electrode material of the high initial coulombic efficiency sodium ion battery of this embodiment are the same as those of Example 1, except that the parameter conditions of the preparation process are different (as shown in Table 1):

[0084] In step 1, the heat treatment time in this embodiment is 4 hours;

[0085] In step 2, the oxidizing atmosphere of this embodiment is composed of 90% Ar2 and 10% H2O; the heat treatment temperature is 500°C, and the heat treatment time is 0.5h.

[0086] XPS detection was performed using the method in Example 1, and it was found that the proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 5.5%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride, and hydroxyl groups, among which the proportion of lactone groups and carboxylic acid anhydride was 71.3%.

[0087] Example 8

[0088] The preparation method and carbon negative electrode material of the high initial coulombic efficiency sodium ion battery of this embodiment are the same as those of Example 1, except that the parameter conditions of the preparation process are different (as shown in Table 1):

[0089] In step 1, the reduction treatment time is 4 h;

[0090] In step 2, the oxidizing atmosphere of this embodiment is composed of 80% Ar2 and 20% CO; the heat treatment temperature is 500°C, and the heat treatment time is 1 hour.

[0091] XPS detection was performed using the method in Example 1. The oxygen atoms in the carbon negative electrode material of this embodiment accounted for 8.3%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, and carboxylic acid anhydride. Among them, the relative content of lactone groups and carboxylic acid anhydride was 82.2%.

[0092] The preparation process and electrolyte of the high first coulombic efficiency sodium ion battery carbon negative electrode material assembled into a sodium ion half-cell in this embodiment are the same as those in Example 1.

[0093] Example 9

[0094] The preparation method and carbon negative electrode material of the high initial coulombic efficiency sodium ion battery of this embodiment are the same as those of Example 1, except that the parameter conditions of the preparation process are different (as shown in Table 1):

[0095] In step 1, the reduction treatment time in this embodiment is 4 hours;

[0096] In step 2, the oxidizing atmosphere composition of the grafting treatment in this embodiment is 78% N2 and 22% O2; the heat treatment temperature is 200°C, and the heat treatment time is 1 hour.

[0097] XPS detection was performed using the method in Example 1. The proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 3.3%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups. Among them, the proportion of lactone groups and carboxylic acid anhydride groups was 73%, and the proportion of carboxyl groups was 2.2%.

[0098] The preparation process and electrolyte of the high first coulombic efficiency sodium ion battery carbon negative electrode material assembled into a sodium ion half-cell in this embodiment are the same as those in Example 1.

[0099] Example 10

[0100] The preparation method and carbon negative electrode material of the high initial coulombic efficiency sodium ion battery of this embodiment are the same as those of Example 1, except that the parameter conditions of the preparation process are different (as shown in Table 1):

[0101] In step 1, the reduction treatment time in this embodiment is 4 hours;

[0102] In step 2, the oxidizing atmosphere composition of the grafting treatment in this embodiment is N2 accounting for 78% and O2 accounting for 22%; the heat treatment temperature is 550°C, and the heat treatment time is 0.5h.

[0103] XPS detection was performed using the method in Example 1. The proportion of oxygen atoms in the carbon negative electrode material of this embodiment was 16.3%, and the oxygen-containing functional groups on the surface of the carbon material were lactone groups, ester groups, carboxylic acid anhydride groups, and carboxyl groups. Among them, the proportion of lactone groups and carboxylic acid anhydride groups was 76.8%, and the proportion of carboxyl groups was 2.3%.

[0104] The preparation process and electrolyte of the high first coulombic efficiency sodium ion battery carbon negative electrode material assembled into a sodium ion half-cell in this embodiment are the same as those in Example 1.

[0105] Comparative Example 1

[0106] Compared with Example 1, this comparative example is different in that the carbon negative electrode material in this comparative example is not subjected to oxidation treatment and is directly assembled into a sodium ion half-cell. Since this comparative example is not subjected to oxidation treatment, the relative content of heterofunctional groups on the surface of the carbon material is 55.1%, and the oxygen atoms in the carbon material account for only 0.8%.

[0107] Comparative Example 2

[0108] Compared with Example 1, this comparative example is different in that the electrolyte composition of this comparative example is ethylene carbonate, ethyl methyl carbonate, and sodium perchlorate, the concentration of sodium perchlorate is 1 mol / L, and the ratio of ethylene carbonate to ethyl methyl carbonate is 50%:50%.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 1 is that the preparation conditions of the carbon negative electrode material are different (as shown in Table 1):

[0111] In step 1, the reduction treatment temperature of this comparative example is 900° C. and the time is 4 h;

[0112] In step 2, the oxidizing atmosphere composition of the grafting treatment in this comparative example is N2 accounting for 78% and O2 accounting for 22%; the grafting treatment temperature is 50°C and the time is 1 hour. XPS detection shows that the proportion of oxygen atoms in the carbon negative electrode material is 0.5%, and the oxygen-containing functional groups on the surface of the carbon material are hydroxyl, carbonyl, and carboxyl, and the relative content of carboxyl is 1%.

[0113] Comparative Example 4

[0114] The difference between this comparative example and Example 1 is that the preparation conditions of the carbon negative electrode material are different (as shown in Table 1):

[0115] In step 2, the oxidizing atmosphere composition of the grafting treatment in this comparative example is 95% N2 and 5% O2; the grafting treatment temperature is 400°C and the time is 0.5h; XPS detection shows that the proportion of oxygen atoms in the carbon negative electrode material is 2.6%, and the oxygen-containing functional groups on the surface of the carbon material are hydroxyl and carbonyl, with a relative content of 86.7%.

[0116] Comparative Example 5

[0117] The difference between this comparative example and Example 1 is that the preparation conditions of the carbon negative electrode material are different (as shown in Table 1):

[0118] In step 2, the oxidizing atmosphere composition of the grafting treatment in this comparative example is 60% N2 and 40% O2; the grafting treatment temperature is 400°C and the time is 0.5h; XPS detection shows that the proportion of oxygen atoms in the carbon negative electrode material is 36.0%, and the oxygen-containing functional groups on the surface of the carbon negative electrode material are carbonyl and carboxyl, among which the carboxyl group accounts for 1.5%.

[0119] Comparative Example 6

[0120] The difference between this comparative example and Example 1 is that the preparation conditions of the carbon negative electrode material are different (as shown in Table 1):

[0121] In step 2, the oxidizing atmosphere of this comparative example is composed of 30% O2, 20% CO and 50% CO2; the heat treatment temperature is 400°C, the heat treatment time is 0.5h, and XPS detection shows that the oxygen atoms in the carbon negative electrode material account for 38.7%, and the oxygen-containing functional groups on the surface of the obtained carbon material are carbonyl and carboxyl, among which the carboxyl group accounts for 0.8%.

[0122] Table 1 Different parameter conditions of Examples and Comparative Examples

[0123]

[0124]

[0125] Test Example 1

[0126] The electrochemical performance of the sodium ion half-cells of Examples 1-10 and Comparative Examples 1-6 was tested, and the initial coulombic efficiency results were shown in Table 2:

[0127] Table 2 Content and performance effect of examples and comparative examples

[0128]

[0129]

[0130] Result analysis:

[0131] It can be seen from the data in Table 2 that the carbon negative electrode material obtained by the reduction treatment and grafting treatment method in this embodiment has a high first coulombic efficiency. Among them, the oxygen atoms of the oxygen-containing functional groups on the surface of the carbon negative electrode material of Example 1 account for 10.6%, and the specific functional groups precisely controlled are lactone groups, carboxylic anhydride groups and carboxylic acid groups with a relative content of 86.6%. The performance of the assembled sodium ion half-cell is the best, and the first coulombic efficiency is as high as 98.6% (such as Figure 2 As shown), it is the best embodiment of the present invention. The thermogravimetric loss curve of Example 1 is as shown Figure 5 As shown, it can be seen that too high a temperature will cause material burning, and the grafting treatment temperature should not exceed 550°C.

[0132] Comparing the results of Examples 2-10 with those of Example 1, it can be seen that in the preparation process of the carbon negative electrode material, although the type and proportion of the grafted functional groups will be changed by changing the grafting treatment temperature, the type of mixed atmosphere and the volume ratio of the oxidizing gas, it does not exceed the specific range. When the obtained carbon negative electrode material comes into contact with the composite electrolyte, the screening interface membrane formed thereby still has the efficient screening ability of simultaneously screening sodium ions and solvent molecules, and still exhibits excellent first coulombic efficiency.

[0133] Comparing the results of Comparative Examples 3-6 with those of Example 1, it can be seen that when the preparation condition parameters are adjusted out of the range, the grafted oxygen-containing functional group is not a single specific functional group, and the proportion of specific functional groups and the total proportion of oxygen atoms in the carbon negative electrode material exceed the range. The screening interface film formed by the obtained carbon negative electrode material and the composite electrolyte has a weak screening ability for sodium ions and solvent molecules, resulting in a significant decrease in the first coulombic efficiency.

[0134] like Figure 6 and Figure 7As shown, compared with the results of Example 1 and Example 2, it can be seen that without using the carbon negative electrode material and composite electrolyte of the present application, the interface film formed does not have the ability of efficient screening, and its first coulombic efficiency is significantly reduced.

[0135] Test Example 2

[0136] The sodium ion half-cells of Examples 1-10 and the sodium ion half-cells of Comparative Examples 1-6 were subjected to cyclic voltammetry tests (sweep rate of 0.2 mV / s, voltage range of 0.005-3 V), and then the corresponding data were obtained at the film formation potential range (0.8-1 V), and Tafel curves were drawn. The Tafel slope was obtained according to the Tafel formula, and the Tafel slope of the film formation reaction of the negative electrode material prepared by the embodiment method was finally obtained to be 40-60 mV dec. -1 , while the Tafel slope of the film-forming reaction prepared by the comparative method is 70-90 mV dec -1 The Tafel slope can usually reflect the film formation speed of SEI. In general, a decrease in the Tafel slope corresponds to an acceleration of the film formation kinetics, which accelerates the SEI film formation speed. Figure 1 As shown, the Tafel slope of the graphene with precise control of specific functional groups (Example 1) is 56.5 mV dec -1 , compared to the Tafel slope of unmodulated graphene (Comparative Example 1) of 76.3 mV dec -1 The significant decrease further illustrates that the specific functional groups precisely controlled and directed implanted on the surface of the carbon negative electrode material obtained by the method of this embodiment can accelerate the construction of the screening interface film.

[0137] In summary, from the results of Test Example 1 and Test Example 2, it can be seen that according to the composition of the composite electrolyte, by selectively controlling the processing temperature, the type of mixed atmosphere and the volume ratio of the oxidizing gas within a certain range, specific functional groups can be grafted, and the ratio of specific functional groups and the total ratio of oxygen atoms in the carbon negative electrode material can be precisely controlled to achieve precise adjustment within the range of specific functional groups of the carbon negative electrode material. The specific functional groups directionally implanted on the surface of the obtained carbon negative electrode material are Lewis strong acids in the solution, can quickly combine with sodium ions in the composite electrolyte, have strong adsorption force, can enhance the adsorption of intermediates, and make the Tafel slope of the film-forming reaction increase from 70 to 90 mV dec. -1 Reduced to 40-60mV dec -1 , further accelerating the construction of the screening interface membrane. The screening interface membrane thus formed has the ability of efficient screening, which can realize the simultaneous screening of sodium ions and solvent molecules, greatly improving the first coulombic efficiency and cycle stability.

[0138] At the same time, the carbon negative electrode material with high first coulombic efficiency of the present invention can also be used as an electrode additive. By adding the carbon negative electrode material of the present invention to the negative electrode of a sodium ion battery, the negative electrode can quickly form a screening-type carbon surface with high-efficiency screening capability, thereby reducing the loss of sodium ions and providing a new method for enhancing the first coulombic efficiency of the carbon negative electrode material of a sodium ion battery.

[0139] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention may be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the foregoing description. It is intended that all variations that fall within the meaning and range of equivalents of the claims be embraced within the present invention. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

[0140] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent replacements, and improvements made to the above embodiments based on the technical essence of the present invention shall be included in the scope of protection of the technical solution of the present invention.

Claims

1. A carbon negative electrode material with high initial coulombic efficiency, obtained by implanting oxygen-containing functional groups on the surface of a carbon material, characterized in that: The oxygen-containing functional groups are specific functional groups that are precisely controlled. The specific functional groups include lactone groups and carboxylic acid anhydrides, and the lactone groups and carboxylic acid anhydrides account for 64% to 87%.

2. The carbon negative electrode material with high first coulombic efficiency according to claim 1, characterized in that: The specific functional groups also include carboxyl groups, and the proportion of the carboxyl groups is 1% to 10%.

3. The carbon negative electrode material with high first coulombic efficiency according to claim 1, characterized in that: The specific surface area of the carbon material is 200 m 2 g -1 ~2000m 2 g -1 , the carbon material includes at least one of graphene, carbon nanotubes, porous carbon, microporous carbon and mesoporous carbon.

4. The carbon negative electrode material with high first coulombic efficiency according to claim 1, characterized in that: The oxygen atoms in the carbon negative electrode material account for 3.3% to 23.1%.

5. A method for preparing a carbon negative electrode material with high initial coulombic efficiency according to any one of claims 1 to 4, comprising reducing and grafting the surface of the carbon material, characterized in that: The grafting treatment is to implant precisely controlled specific functional groups in a mixed atmosphere, wherein the mixed atmosphere includes an oxidizing atmosphere and a non-oxidizing atmosphere, and the volume of the oxidizing atmosphere accounts for 10-30% of the total volume of the mixed atmosphere; the temperature of the grafting treatment is 200-550°C, and the time is 0.5-2 hours; The oxidizing atmosphere includes at least one of oxygen, carbon monoxide, water vapor and ozone; and the non-oxidizing atmosphere includes at least one of nitrogen, argon and hydrogen.

6. The method for preparing a carbon negative electrode material with high initial coulombic efficiency according to claim 5, characterized in that: The reduction treatment is carried out in an inert gas atmosphere, the reduction temperature is 500° C. to 1000° C., and the reduction time is 2 to 4 hours.

7. An application of the carbon negative electrode material with high initial coulombic efficiency according to any one of claims 1 to 4 directly as a carbon negative electrode in a sodium ion battery, or indirectly as a negative electrode additive in combination with other carbon material negative electrodes in a sodium ion battery.

8. The use according to claim 7, characterized in that The sodium ion battery also includes an electrolyte, which is a composite electrolyte containing a sodium salt and an organic solvent, wherein the sodium salt includes at least one of sodium trifluoromethanesulfonate, sodium perchlorate and sodium hexafluorophosphate; and the organic solvent includes at least one of methyl carbonate, ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

9. The use according to claim 8, characterized in that A sieving type interface film is formed between the carbon negative electrode material and the composite electrolyte, and the Tafel slope of the film forming reaction is 70 to 90 mV dec. -1 Reduced to 40-60mV dec -1 .

10. The use according to claim 8, characterized in that The sieving type interface film is formed by the contact reaction between the carbon negative electrode material and the composite electrolyte on the carbon surface, and includes organic components and inorganic components; wherein the organic component includes at least one of sodium alcohol, alkyl carbonate, ester polymer and ether polymer; the inorganic component includes at least one of sodium oxide, sodium carbonate, sodium fluoride and sodium sulfonate.

Citation Information

Patent Citations

  • Method for rapidly preparing carbon microspheres by using cotton cellulose

    CN102633249A

  • Carbon material applied to negative electrode of lithium ion power battery and preparation method of carbon material

    CN103325997A

  • Direction control method of surface oxygen functional groups on coal-based hard carbon for sodium-storing cathodes

    CN109796003A

  • Biomass-based sodium ion battery negative electrode material as well as preparation method and application thereof

    CN117963880A

Cited By

  • Mesoporous carbon material, preparation method thereof, lithium ion battery and electric device

    CN122704887A